Flexible Dual Fe-based Catalyst: MIL-53(Fe) Loaded with Deep Eutectic Solvent for Discontinuous Selective Oxidation of H2S - Fengke Wang; Chaofan Li; Weizhen Kong; Shucan Qin; Qianqian Peng; Lihua Zang; Yunqian Ma; Yi Nie; Guihuan Yan (Aerosol and Air Quality Research)
Abstract Deep eutectic solvent (DES) as the guest molecule and flexible Metal-organic framework (MOF) as the supporting material can be used to provide an efficient catalyst: flexible dual Fe-based DES@MOF, which can efficiently remove H2S in discontinuous removal process (100–180°C). The materials were characterized by XRD SEM, FT-IR, BET, XPS, TG, CV and Py-FTIR. According to the result, MOF (MIL-53(Fe)) incorporating 30 wt% DES (ChCl/FeCl3) exhibited the best H2S removal performance at 180°C, with the H2S removal capacity of 2527 mg mL−1 (3744 mg g−1). And the H2S removal capacity reduced by 9% after two cycles of thermal regeneration. The process of desulfurization includes two stages: catalytic oxidation and adsorption, which are determined by the Fe3+ in DES and the structural characteristics, such as the aggregation of mesopores, respectively. For MIL-53(Fe), FeOOH as an intermediate and Lewis acid sites also played a catalytic role. Elemental sulfur was the predominant product with a small amount of sulfate. Both elemental sulfur and DES can induce the flexible deformation of MOF as the guest molecule to relieve the passivation of catalyst.